Oligopoly Modeling between Public and Private Companies with Complementarity - Chun-Hung Chen (Discrete Dynamics in Nature and Society)
This study investigated the coexistence of public and private companies using a complementary model to explore mixed oligopoly strategies. Compared to the traditional theory of mixed oligopoly, the main difference of this study is that it revealed that the products produced by both companies are completely complementary. The five findings of the study were as follows: First, under the premise of having one firm classified as a public firm, although it can reach the equilibrium of the maximum solution for social welfare, this causes a loss. Second, more seriously, the private firm would view this as a huge incentive and aggressively pursue to be the price leader, which may result in a greater loss for the public firm. Third, the asymmetry of the model of the complementary mixed oligopoly is of note; that is, when the private firm is in aggressive pursuit to be the price leader, it can elevate its profit margin, but when the public firm is aggressively pursuing be the price leader, this would not result in better profits. Fourth, if the public firm is under budgetary constraints, then the private firm would have no incentive to aggressively pursue being the price leader. Fifth, if the price of the product between the public firm and the private firm is a “strategic substitute,” the coexistence of the public firm and the private firm will be better than total privatization.